FRI0640-HPR Effects of Postural Taping on Pain and Function Following Osteoporotic Vertebral Fractures – A Pilot Study. (15th July 2016) - Palmer, S.; Lewis, R.; Barnett, S.; Cramp, M.; Berry, A.; Thomas, A.; Clark, E.
Abstract : Background: Osteoporotic Vertebral Fractures (OVFs) are common and present a significant burden to patients and healthcare services. It is known that poor posture (such as forward flexion) can increase the pressure on vertebrae, increasing pain and the risk of further fracture. Postural taping may therefore act to reduce spinal loading and pain. Objectives: To assess the effects of postural taping on pain and function when used for a 4-week period in addition to usual care. To decide if a fully-powered study is feasible. Methods: Recruitment: Men and women with OVFs recruited from two local healthcare organisations. Inclusion criteria: At least one painful OVF; Fracture not immobilised; Independently mobile (with or without an aid); Able to apply taping device independently or with assistance. Exclusion criteria: Osteoporosis secondary to metabolic bone disorders or other disease (steroid-induced osteoporosis was not an exclusion); Fragile or broken skin; Known allergy to adhesive plasters; Vertebroplasty or kyphoplasty. Diagnosis was confirmed by a consultant rheumatologist. A mutually convenient appointment was agreed when participants gave formal consent and completed baseline questionnaires. Outcome measures: Outcomes were assessed at baseline and at 4 weeks. Pain: Visual Analogue Scale (VAS) for pain on movement and at rest. Function and Quality of Life: Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO). Intervention: Following baseline assessment, participants were randomly allocated to receive the taping device ("PosturePlast") for home use and received full instruction (including skin care) and a supply of devices. The taping device is like a large sticking plaster with a built-in flexible plastic "X". The manufacturer claims it controls back movement, reduces pain and improves posture. Those randomised to the control condition continued with usual care. Results: 25 participants took part (taping n=13, control n=11). The groups were comparable in terms of age and time between assessments, although the control group contained more men (n=3 versus n=0) and scored slightly lower on most clinical scores. Descriptive analysis showed fairly consistent improvements in outcomes in both groups. The mean difference favoured the taping group for most outcomes. Generally the observed standardised effect sizes were small to medium (see Table). The largest effects were evident for pain and physical function. As might be expected in a small study, the observed mean group differences were associated with large confidence intervals. Conclusions: The taping device has the potential to improve pain and function, which is notable for such a simple device. However the findings need to be replicated in an appropriately powered study. The study procedures were acceptable to most participants and it seems that a definitive trial is feasible. Acknowledgement: Supported by the North Bristol NHS Trust Springboard Fund and the National Osteoporosis Society. Research Ethics Committee reference 13/WM/0357. Disclosure of Interest: None declared